“As Chrysididas do Brazil”: A catalogue of the Brazilian cuckoo wasps (Hymenoptera: Chrysididae) - Lucena, Daercio A.A. [UNESP]; Gomes, Rayane Sales; Zanella, Fernando C.V.; Almeida, Eduardo A.B. (FapUNIFESP (SciELO), 2024)
We present an updated, commented, and revised catalog for the Brazilian cuckoo wasps (Hymenoptera: Chrysididae) and pay tribute to Adolph Ducke’s 1913 monographic work on the Brazilian fauna of these wasps titled “As Chrysididas do Brazil.” We document all 159 chrysidid species known to occur in Brazil, classified into 18 genera representing three subfamilies: Amiseginae, Chrysidinae, and Cleptinae. We detail all synonyms, provide geographical distribution for all recorded species, and compile host associations for 28 species in Brazil. Notes on type specimens and their depository collections are provided and complemented by images of 30 primary types. Additionally, we reinstated Exsecochrysis Linsenmaier from the synonymy with Pleurochrysis Bohart (rejected junior homonym) in place of Rhipidochrysis Rosa & Pavese, new synonym. All species previously treated as Pleurochrysis are transferred to Exsecochrysis.
Keywords: Chrysidoidea; Diversity; Geographic distribution; Neotropical; Taxonomy